Peningkatan Hasil Belajar Peserta Didik pada Pembelajaran Pendidikan Pancasila dengan Model Problem Based Learning (PBL) di Kelas IV SDN 23 Payakumbuh - Hermawan, Thoriq; Arwin, Arwin (Lembaga Yasin AlSys, 2025)
This study is motivated by the low learning outcomes of students in the Pancasila Education subject, which are partly attributed to suboptimal teaching processes and limited student engagement. The purpose of this research is to describe the improvement in learning outcomes through the implementation of the Problem-Based Learning (PBL) model among Grade IV students at SDN 23 Payakumbuh. The method used is Classroom Action Research (CAR) conducted in two cycles, each comprising the stages of planning, implementation, observation, and reflection. The research subjects included one teacher and 19 students (14 boys and 5 girls). Data collection techniques involved observation, tests, and non-test instruments. The results show that the application of the PBL model led to significant improvements across various aspects of learning. The quality of teaching modules increased from 88.88% in Cycle I to 94.44% in Cycle II, categorized as “Excellent.” Teacher activity improved from 83.92% to 96.42%, while student activity increased from 80.35% to 92.85%. Moreover, the average student learning score rose from 77.03 in Cycle I to 86.88 in Cycle II. These findings demonstrate that the PBL model is effective in enhancing Pancasila Education learning outcomes at the elementary level by promoting more active, contextual, and student-centered learning.